Watch and Learn? Using EDpuzzle to Enhance the Use of Online Videos. (September 2019) - Mischel, Leann J.
As the use of videos for learning increases, the need to better use the viewing experience also increases. EDpuzzle is a video-sharing program that offers instructors a way to enhance the use of online videos for learning. It allows instructors to ensure that students have viewed the lesson in its entirety and determine whether they understood its content. The author has used EDpuzzle in undergraduate general business and entrepreneurship classes for homework assignments and has received positive feedback from students about it. Discussions with students have indicated that the use of EDpuzzle helped them focus more on the important aspects of the videos and that they were more confident of their learning after taking embedded quizzes. The qualities EDpuzzle offers are discussed here with particular emphasis on understanding how the application can be used to enhance the use of online videos along with its advantages and disadvantages.